The influence of macrotexture of limestone aggregates on pavement skid resistance / Noorul Fahame Mohd Rodzi - Mohd Rodzi, Noorul Fahame (2005)
It is the aim of the highway engineer to make economic, durable and safe roads. The Polished Stone Value (PSV) of aggregates gives a measure of resistance to the polishing action vehicle under tire under conditions similar to those occurring on the surface of a road. The action of road vehicle tire on road surfaces result in polishing at the top and exposed aggregate surface. The state of polish is one of the main factors affecting the resistance to skidding. Resistance to this polishing action is determined principally by the inherent qualities of the aggregate itself. The study focused on the measuring of the Skid Resistance Value of limestone aggregate from quarries in Perlis and Perak. To achieve this, four different sizes of samples of limestone was assessed from four quarries (2 Perlis and 2 Perak).The quarries are Pens Industries Sdn. Bhd. (Perlis) - Ql, Chua Teong Chai & Sons Quarry Sdn. Bhd (Perlis) - Q2, Anting Sdn Bhd (Perak) - Q3, Sri Gapis Quarry Sdn Bhd (Perak) - Q4. Petrographic is to determine from the petrographic examination. There are five different type of testing to determine the aggregates properties, which are Los Angeles Abrasion Test, Aggregates Impact Value, Aggregates Crushing Value Test, Flakinest Index Test and Specific Gravity Test. Los Angeles Abrasion Test is to ascertain the degration of aggregates by abrasion and impact. Aggregates Impact Value test is to determine the aggregates impact value of the aggregate. The Aggregates Crushing Value Test is to ascertain the hardness of the aggregate. For Flakinest Index Test is to determine the flakinest index of aggregates and Specific Gravity Test is to determine the specific gravity of the aggregates The result of Skid Resistance for every quarry has shown some significant value. Wet aggregates reduce the skid resistance of the texture and are very dependent on the surface type. The action between the surface tires will effect at the top and exposed aggregates surface. The relationship of Skid Resistance and Texture Depth is to determine relation between value of skid resistance and the texture depth of Limestone aggregates.